2018
DOI: 10.1097/aln.0000000000002184
|View full text |Cite
|
Sign up to set email alerts
|

Averting Opioid-induced Respiratory Depression without Affecting Analgesia

Abstract: The ventilatory control system is highly vulnerable to exogenous administered opioid analgesics. Particularly respiratory depression is a potentially lethal complication that may occur when opioids are overdosed or consumed in combination with other depressants such as sleep medication or alcohol. Fatalities occur in acute and chronic pain patients on opioid therapy and individuals that abuse prescription or illicit opioids for their hedonistic pleasure. One important strategy to mitigate opioid-induced respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 120 publications
(201 reference statements)
1
100
1
Order By: Relevance
“…To determine whether respiratory stimulants can reverse respiratory depression by opioids in larval zebrafish, we tested two types of agonists targeting excitatory receptors: ampakines which comprise drugs acting on AMPA receptors (Ren, Poon, Tang, Funk, & Greer, 2006) and serotoninergic agents (Manzke et al, 2003). CX-614, an ampakine allosteric modulator of AMPA receptors, did not reverse respiratory depression in our larval zebrafish models, which is not consistent with its effects in rodents (Ren et al, 2006) or humans (Dahan et al, 2018). This lack of ampakine effects may be due to the low concentration used in this study because higher doses of CX-614 were inducing severe seizures in larval zebrafish (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…To determine whether respiratory stimulants can reverse respiratory depression by opioids in larval zebrafish, we tested two types of agonists targeting excitatory receptors: ampakines which comprise drugs acting on AMPA receptors (Ren, Poon, Tang, Funk, & Greer, 2006) and serotoninergic agents (Manzke et al, 2003). CX-614, an ampakine allosteric modulator of AMPA receptors, did not reverse respiratory depression in our larval zebrafish models, which is not consistent with its effects in rodents (Ren et al, 2006) or humans (Dahan et al, 2018). This lack of ampakine effects may be due to the low concentration used in this study because higher doses of CX-614 were inducing severe seizures in larval zebrafish (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
“…Such approach has the potential to validate many drug candidates without making any assumptions on their mechanisms of action or targets. Our drug discovery approach proposes to test whether drugs or combinations of drugs can be used as analgesics without the side-effects of respiratory depression and such strategy is of considerable interest (Dahan et al, 2018; (Montandon & Slutsky, 2019). We combined several assays to test the respiratory depressant effects of pain killers and their analgesics properties.…”
Section: Discussionmentioning
confidence: 99%
“…The second question has recently been addressed by Jonkman et al [64]. They showed that ketamine effectively counteracts opioid-induced respiratory depression, possibly through its (indirect) actions at the AMPA receptor [65]. This is an important observation that is relevant in perioperative care as well in NP patients treated with (high dose) opioids.…”
Section: Expert Opinionmentioning
confidence: 99%
“…GAL-021 has recently been developed as a novel breathing control modulator thought to preserve respiratory drive and to protect patients from the respiratory impairment resulting from opioids and other modalities; moreover, it notably did not influence analgesia [1][2][3][4][5][6][7]. The studies have also reported that this agent is an experimental drug demonstrated to inhibit Ca 2+ -activated K + channels with big conductance functionally expressed on type 1 cells of the carotid bodies [1,8,9].…”
Section: Introductionmentioning
confidence: 99%